FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PELAPORAN LAPORAN KEUANGAN PADA PERBANKAN KONVENSIONAL DI BEI - Putri, Shania Aili; Salim, Susanto (Jurnal Paradigma Akuntansi, 2025)
This study aims to empirically analyze the effects of the variables on profitability, leverage, company size, liquidity and reputation of public accountings firms (KAP) on conventional banks listed on the Indonesia Stock Exchange in 2019-2021. The sample used in this study was 96 data. The samples selected using purposive sampling method and valid data are 32 companies. Data processing in this study uses EViews 12. The results of this study indicate that there is a non-significant positive effect between profitability and KAP’s reputation on the timeliness of financials report reporting. Leverage, company size and liquidity, on the other hand gives a negative but insignificant affect the timeliness of financial reporting.